DIALECTICS IN RELATIONSHIP BETWEEN RELIGION AND STATE: A CORRELATION OF RELIGIOUS PRINCIPLES AND IDEALS OF LAW IN INDONESIA - Abidin Nurdin (Al-Bayyinah, 2020)
Thearticle discusses the dialectics in the relationship between religion and state in its correlation with the ideals of law in Indonesia, which is focused on the variants and principles of religion in the state. There are three variants regarding the relationship between religion and state namely, integralistic, secularistic and symbiotic. Indonesia as a state based on Pancasila which upholds religious values can be included in symbiotic variants. Religious principles in symbiotic variants can be implemented because they do not conflict with Pancasila and the 1945 Constitution of Republic of Indonesia. Between Islam and the ideals of law, in this case Pancasila, is not a contradictory entity but two elements that are in line. These principles are power as trust, deliberation, justice, equality, protection of human rights and independent justice; be valid proof so that the state can be said to be a nation that upholds human dignity and benefits. As a symbiotic state, Islamic law has room in the state, namely as one source of national law. The implication of this study is that between the state and religion there is no conflict, religion is not alpha in providing interpretations about the state. Therefore, between religion and state is not a new thing because the ideals of law and religious values have the same hope that is to achieve mutual benefit.Keywords: Religion; State; Principle, Ideals of Law.